Comparative Analysis of Bioactive Compounds in Stingless Bee Honey from Wetland and Non-Wetland Vegetation - Fajari, Nanang Miftah; Hamidah, Siti; Suhartono, Eko; Pranoto, Agung; Perdanakusuma, David Sontani; Hasrianti, Nuvita; Agustina, Laily; Raharjo, Kevin Prasetya (HAYATI Journal of Biosciences, 2026)
Stingless bee honey (SBH) produced by the stingless bee species Heterotrigona itama in South Kalimantan is a biologically active natural product with therapeutic potential. This study examines differences in bioactive compounds—molecules that affect living organisms—between SBH from wetland and non-wetland vegetation. The goal is to show how a terrestrial landscape influences functional properties. Using untargeted metabolomics, a technique for surveying many small molecules without preselection, via LC-HRMS (Liquid Chromatography-High-Resolution Mass Spectrometry), we identified 141 distinct metabolites (small molecules involved in metabolism), with 23 compounds present in all samples. These shared metabolites support the mitigation of obesity, wound healing, cardiovascular health, neuroprotection, and gastrointestinal function. Hierarchical cluster analysis, a statistical method for grouping data, using retention time (the time a compound takes to pass through the system), area (the size of the signal on the detector), and molecular weight, revealed distinct compositional clusters between wetland- and non-wetland-derived SBH, suggesting vegetation type shapes metabolite profiles. Wetland SBH contained 198 compounds, while non-wetland samples had 193. These findings highlight how ecological origin modulates the bioactive compounds in SBH and influences their use in nutraceuticals (foods with health benefits) and functional foods. By establishing a metabolomic baseline for SBH, this work advances understanding of its region-specific health benefits and underscores the importance of ecosystem-conscious apiculture (beekeeping) in optimizing bioactive yield.